Pedicle Subtraction Osteotomy Versus Multiple Posterior Column Osteotomies in Severe and Rigid Neuromuscular Scoliosis. Issue 15 (1st August 2018) - Bekmez, Senol; Ozhan, Mehmet; Olgun, Zeynep Deniz; Suzer, Anil; Ayvaz, Mehmet; Demirkiran, Halil Gokhan; Karaagaoglu, Ergun; Yazici, Muharrem
Abstract : Study Design: Retrospective analysis. Objective: The aim of this study is to compare the safety and efficacy of the apical pedicle subtraction osteotomy (PSO) technique with multiple posterior column osteotomies (PCOs) in nonambulatory patients with severe, rigid neuromuscular scoliosis. Summary of Background Data: Neuromuscular scoliosis frequently causes intolerance to sitting due to pelvic obliquity, trunk decompensation, and associated back and rib impingement pain which diminish the patient's functional capacity. In the case of rigid curves, spinal osteotomy techniques are occasionally required for effective correction. Methods: We retrospectively reviewed our patients with severe and rigid neuromuscular scoliosis with associated pelvic obliquity who were treated with posterior instrumented fusion extending to pelvis with more than 1-year postoperative follow-up. We compared radiological and clinical results of PSO and multiple PCO techniques in severe rigid neuromuscular scoliosis with pelvic obliquity of more than 15° in traction radiograph under general anesthesia. Hospital records were also reviewed for operative time, intraoperative blood loss, amount of blood transfusion, duration of hospital stay, and complications. Results: There were 12 patients in the PSO group and 10 patients in the PCO group. There was no significant difference between groups in terms of major curve magnitude, sagittal parameters or pelvic obliquity. Although not statistically significant, PSO technique did trend toward better scoliosis correction (post-op Cobb angle 56.1° vs. 66.7° [ P = 0.415]). PSO technique provided a significantly better correction in pelvic obliquity (59% vs. 84%) ( P = 0.001). There was no significant difference in average intraoperative blood loss, transfusion, and operative times including anesthesia time, hospital stay, or complications. Conclusion: PSO may be an option in correction of severe and rigid neuromuscular scoliosis. It provides better correction of pelvic obliquity without increasing operative time, need for transfusion, or duration of hospitalization as compared to multiple apical PCO technique. Traction radiograph under general anesthesia is a valuable tool in surgical decision making. Level of Evidence: 4